HEAD AND NECK SURGERY - Ferris, Robert L. (2014)
The first volume of Master Techniques in Otolaryngologic Surgery focuses on the procedures used in Larynx, Hypopharynx, Oropharynx, Oral Cavity and Neck surgeries. The Master Techniques in Otolaryngologic Surgery Series provides "how-to" guides to both the common and advanced procedures performed in the major subspecialties of Otolaryngologic Surgery. Step-by-step instructions and over 300 full-color intraoperative photographs and line drawings makes this guide an excellent reference for Head and Neck specialists and General Otolaryngologists alike. Each procedure follows the series format and scope for clear step-by-step instruction to each technique. Written by experts in the field from around the world Covers both common and advanced procedures. Over 300 full-color photographs and drawings. Companion website with full-text and supplemental video segments that showcase key techniques. The second volume focuses on the procedures used in Thyroid, Parathyroid, Salivary Glands, Paranasal Sinuses and Naspoharynx With contributions from the world's leading experts, this book is a true g2show-tog3s guide to the common and advanced procedures in the major subspecialties of Otolaryngologic Surgery. Step-by-step instructions and over 250 full-color intraoperative photographs and line drawings makes this guide an excellent quick reference for Head and Neck specialists and General Otolaryngologists alike. Each procedure follows the series format and scope for clear step-by-step instruction to each technique. Written by experts in the field from around the world. Covers both common and advanced procedures. Over 250 full-color photographs and drawings. Companion website with full-text and supplemental video segments that showcase key techniques.
v. 1. Larynx, hypopharynx, oropharynx, oral cavity and neck -- v. 2. Thyroid, parathyroid, salivary glands, paranasal sinuses, and nasopharynx.
Title on electronic resource for volume 1: Master techniques in otolaryngology : head and neck surgery : larynx, hypopharynx, oropharynx, oral cavity and neck.
Title on electronic resource for volume 2: Master techniques in otolaryngology : head and neck surgery : thyroid, parathyroid, salivary glands, paranasal sinuses, and nasopharynx.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Head -- Surgery; Neck -- Surgery; Otolaryngology, Operative; Head -- surgery; Neck -- surgery; Otorhinolaryngologic Diseases -- surgery; Head and Neck Neoplasms -- surgery; Ophthalmologic Surgical Procedures -- methods; Oral Surgical Procedures -- methods; Otorhinolaryngologic Surgical Procedures -- methods; Print books